2012
DOI: 10.14419/ijet.v2i1.534
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of electron number density and temperature of laser-induced Silver plasma

Abstract: Silver (Ag) plasma generated by second harmonics (532 nm) using Nd:YAG laser has been investigated at 17.6 mJ and 88.6 mJ energy level. The spatial behavior of the END and Electron Temperature (ET) was measured at ambient air pressures at different energy level and distance ranging from 0-4.5 mm form the target metal. The ET's were found to be varies from 17895 K to 10593 K, while END was found to be 2.229  10 15 to 6.44  10 14 cm -3 and 1.76  10 16 to 1.893  10 15 cm -3 for 17.6 mJ and 88.6 mJ energy, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…Most of the peaks appeared within the range of (160 to 280 nm), except for some peaks belonging to Ag I (at 338.62 nm). This result is agreement with Musadiq et al [12]. The emission spectrum intensity increase with increasing laser energy.…”
Section: Fig 3: the Variation Of (A) T E And (B) N E With Laser Enersupporting
confidence: 93%
“…Most of the peaks appeared within the range of (160 to 280 nm), except for some peaks belonging to Ag I (at 338.62 nm). This result is agreement with Musadiq et al [12]. The emission spectrum intensity increase with increasing laser energy.…”
Section: Fig 3: the Variation Of (A) T E And (B) N E With Laser Enersupporting
confidence: 93%
“…Whereas, at larger distances, the slow variation is due to the recombination of electrons and ions. Similar observations on the spatial evolution of Ag plasma characteristics have also been reported by Musadiq et al, 23 who investigated the spatial behavior of Ag plasma produced by 532 nm of Nd:YAG laser. It is evident from Fig.…”
Section: B Spatial Evolution Of Ag Plasmasupporting
confidence: 85%
“…Rashid et al 22 reported the comparative study on the effect of the inter-pulse delay and the ratio of the laser pulse energies on the silver emission line intensities, enhancement for collinear and orthogonal pre-ablation dual pulse configurations using the 1064 and 532 nm of Nd:YAG lasers. Recently, Musadiq et al 23 reported the effect of different pulse energies of 532 nm Nd:YAG laser on the fundamental plasma parameters and on the spatial behavior of silver plasma from 0 to 4.5 mm from the target surface. The objective of the present work was to characterize the laser induced silver plasma in terms of spectral line intensities and plasma parameters (n e and T e ) under different experimental conditions using the LIBS technique.…”
Section: Introductionmentioning
confidence: 99%
“…There is a moderate body of work diagnosing space and time resolved optical emission from silver LPP plumes [12][13][14][15][16] for a range of experimental conditions and laser intensities. Previously, Issac et al 12 studied the dynamics of laser produced Ag plasma as a function of Ar ambient pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Shuaibov et al 14 studied time-averaged energy distributions and recombination times of Ag atoms. Musadiq et al 15 measured electron densities and temperatures from the timeintegrated spectra at different laser energies. Esposito et al 16 studied the Ag + dynamics of the pulsed laser ablation of Ag by using Langmuir probe and quadrupole mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%